2019
DOI: 10.1107/s1600576719011580
|View full text |Cite
|
Sign up to set email alerts
|

A simple correction for the parallax effect in X-ray pair distribution function measurements

Abstract: Total scattering and pair distribution function (PDF) analysis has created new insights that traditional powder diffraction methods have been unable to achieve in understanding the local structures of materials exhibiting disorder or complex nanostructures. Care must be taken in such analyses as subtle and discrete features in the PDF can easily be artefacts generated in the measurement process, which can result in unphysical models and interpretation. The focus of this study is an artefact called the parallax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Measured intensities should generally be kept well below the saturation levels, as trapped excited states can remain after long periods of high exposure, leading to unwanted features in the pixel response that must be removed . Other considerations may be necessary for other detection technologies such as Si and CdTe hybrid photon counting detectors. , Diffraction images must be calibrated and corrected for polarization, spatial distortions, , unequal pixel response and parasitic scattering effects . It is further important to apply proper masking of the images to remove anomalously dark or bright pixels, dead pixels, discrete diffraction spots caused by a poor powder average, or other effects such as shadows from any equipment located in the cone of diffracted radiation.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…Measured intensities should generally be kept well below the saturation levels, as trapped excited states can remain after long periods of high exposure, leading to unwanted features in the pixel response that must be removed . Other considerations may be necessary for other detection technologies such as Si and CdTe hybrid photon counting detectors. , Diffraction images must be calibrated and corrected for polarization, spatial distortions, , unequal pixel response and parasitic scattering effects . It is further important to apply proper masking of the images to remove anomalously dark or bright pixels, dead pixels, discrete diffraction spots caused by a poor powder average, or other effects such as shadows from any equipment located in the cone of diffracted radiation.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…Specifically, the thickness of the scintillator and the mounting design can have large effects on the magnitude of the parallax and topography distortions introduced by a detector. It has been shown by many published reports that it is necessary to correct these distortions in the traditional geometry in order to measure and analyze X-ray scattering patterns properly (Weiß et al, 2012;Lu ¨thi et al, 2019;Marlton et al, 2019;Wu et al, 2002;Zaleski et al, 1998). Equivalently, it was observed that implementing the PE-1621 in the inclined geometry similarly necessitated distortion corrections for proper measurement and analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve the desired counting statistics and fast acquisition times, two-dimensional digital flat-panel area detectors are commonly used when performing X-ray total scattering measurements (Marlton et al, 2019). Traditional detector geometries have the incident X-ray beam normal to the detector surface, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is associated with X-ray photons traversing multiple detector pixels at high 2 angles for detectors with thick sensors. Detector parallax also results in peak position and peak shape artefacts; the former can be corrected using a simple quadratic polynomial as demonstrated by Marlton et al (2019).…”
Section: Parallax Artefactmentioning
confidence: 99%